Outcome of peripheral T-cell lymphoma in first complete remission: a Danish-Swedish population-based study. Issue 12 (2nd December 2017) - Cederleuf, Henrik; Hjort Jakobsen, Lasse; Ellin, Fredrik; de Nully Brown, Peter; Stauffer Larsen, Thomas; Bøgsted, Martin; Relander, Thomas; Jerkeman, Mats; El-Galaly, Tarec Christoffer
Abstract: In the present study, we investigate the outcome of 109 Danish and 123 Swedish patients with nodal PTCL in first complete remission (CR), and examine the impact of imaging-based follow-up (FU) strategies. The patients were selected by the following criteria: (a) newly diagnosed nodal PTCL from 2007 to 2012, (b) age ≥18 years, and (c) CR after CHOP or CHOEP therapy. FU guidelines in Sweden included symptom assessment, clinical examinations and blood tests at 3–4-month intervals for 2 years. FU strategies in Denmark was similar but included routine imaging, usually every 6 months for 2 years. Patients had fully comparable characteristics. Overall survival (OS) estimates for patients in CR were similar for all patients ( p = .6) and in PTCL subtypes. In multivariate analysis, country of follow-up had no impact on OS. However, despite continuous CR for ≥2 years, the OS of PTCL remained inferior to a matched general population.